Galicja Wschodnia w traktatach powersalskich i ryskim - Galuba, Rafał (Instytut Historii PAN, 2024)
The conflict over Eastern Galicia and the eastern border of the Poland was one of the most difficult for an independent Polish state. Its dissolution was influenced by the decisions of the Supreme Council of the Peace Conference in Paris, the Treaty of Versailles, the Treaty of Saint-Germain-en-Laye, and the Treaty of Riga. The tragic stage of this conflict was the bloody war between Poland with the Galician Ukrainians and then with Soviet Russia. The Entente’s indecisive policy negatively influenced the conflict, which, from 1918 to 1923, hoped for the reconstruction of white Russia.
p. 81-97
Summary in English.
Keywords: Eastern Galicia; Poland; Conference of Ambassadors; Supreme Council of the Peace Conference in Paris; Treaty of Versailles (1919); Treaty of Saint-Germain-en-Laye; Treaty of Riga; Galician Ukrainians; Curzon Line